Исправления - ФНТ Editorial (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Исправления к статье A. I. Erenburg, Yu. V. Bomze, N. Ya. Fogel, A. Yu. Sipatov, A. I. Fedorenko, V. Langer,M. Norel "Structural investigations of superconducting multilayers consisting of semiconducting materials" (ФНТ 27, с.127-130 (2001)).